Consumer Preferences for Farmed Seafood: An Italian Case Study. Issue 5 (27th May 2020) - Pulcini, Domitilla; Franceschini, Simone; Buttazzoni, Luca; Giannetti, Cristina; Capoccioni, Fabrizio
ABSTRACT: European consumers prefer wild over farmed aquatic food and consider it healthier and tastier. Consumers are increasingly paying attention to sustainability and welfare of farmed fish. Such expectations might be met by organic certification, but this represents a cost for the producer. It is crucial to know consumer habits about farmed aquatic food consumption and willingness to pay for certification. Data about Italian consumers' preferences regarding farmed organic aquatic food were collected by an online questionnaire. A total of 8, 657 answers were analyzed, patterns associated with demographics were investigated, and the degree of correlation among answers was calculated. The majority (75%) of family units buy less than 2 kg of farmed aquatic food per month, spending on average 20–50 €. About 40% never consume organic aquaculture products because of lack of knowledge, unavailability, and high price. Slightly over half (55%) of consumers, regardless of age, sex, and area, were willing to pay a premium price for organic-certified aquatic food, seen as antibiotic free, traceable, and sustainable. Organic food in general is well known, and distrust is the main reason that consumers avoid it, while organic aquatic food is still in its infancy, and lack of knowledge is associated with low consumption.